Panorama e vantagens do uso de análogos de reservatório de águas profundas, exemplo da Fm. Calumbi, campo cidade de Aracaju, bacia de Sergipe-Alagoas (SE) - Hernández, Germán Meneses (2019)
The study of outcrops as hydrocarbon reservoir analogues has been widely used over the last 40 years in the petroleum industry for being a powerful tool for data acquisition, improving in this way the elaboration of detailed models of sub-surface reservoirs. The study of outcrops provides valuable information and allows qualitative and quantitative assessment of sedimentary bodies dimensions and geometries in sub-seismic scale in lateral and vertical discontinuities that are impossible to establish in sub-surface hydrocarbon reservoirs due to the low resolution of the seismic data and well petrophysics. In Brazil more than 80% of all oil is produced from deep water marine deposits, which are the most abundant reservoirs and therefore important targets of the oil industry. The analogues have become important for the understanding of reservoirs and can help in the construction of geological models with more precise representations. The aim of the present contribution was: 1) Illustrate in detail the general outline of the characterization of outcrops as subsurface reservoir analogues, discussing the evolution and research methods, tools used, trends, evolution, theoretical references and gaps. 2) Determine the location (space and geological time) of the ideal outcrop with seismic data and paleontological data available to characterize a reservoir located in the southern part of the Sergipe Alagoas basin. 3) Characterize the outcrop in detail with the use of portable gamma ray spectrometry to establish the possible correlation with data from deep wells drilled in a mature producing field. The results showed that reservoir analogues try to reduce uncertainties, but success in using them depends on a deep evaluation and critical assessment of the scale problems and key objectives involved. Most of the studies discuss the use of the possible candidate for analogous outcropping, but do not apply directly to the sub-surface reservoir modeling. Tectonics does not appear to be a limitation or selection criterion for modeling from outcrop data. The combination of facies analysis and petrophysical data (gamma rays) can provide valuable information on layer thickness, geometry, lithology and assist in understanding subsurface reservoirs. The connection between the oil field Cidade de Aracaju and the analogous outcrop suggests a lateral continuity of the reservoir, which may show changes in its properties depending on the thickness. The results of the outcropping, whose continuity was interpreted from seismic, suggests sedimentary processes characteristic of the marine platform in the shoreface and offshore region. This context contrasts with the interpretations of the ANP for the oil field Cidade de Aracaju, which suggests an environment between the slope and the abyssal plain for the Calumbi Formation in the study area.